Penerapan Teknik Supervisi Observasi Kelas Untuk Meningkatkan Kinerja Guru Dalam Pembelajaran di SD Negeri 94 Tiroang Kabupaten Pinrang Sulawesi Selatan - Andi Hery Harjum (Publikasi Pendidikan, 2018)
This research aims to improve the teachers' performances in learning through supervision with classroom observation technique performed by the principal. This research is a qualitative research. The kind of research used is action research. The steps that have been done in this research were planning, implementation and observation, reflection and revision. The data obtained from interview, observation, and documentation. The results of research showed that; First, the preparation of supervision of classroom observation by the principal become better which was in accordance with the preparation theories of supervision by using classroom observation technique. Second, the implementation process of supervision of classroom observation by the principal has done very well, it causes a conducive atmosphere and enjoyable for teachers and students. Third, the feedback meeting of supervision of classroom observation by the principal carried well so that it can motivate teachers to improve their performances which were in accordance with the feedback meeting theories of supervision by using the classroom observation technique. Fourth, the teachers' performances in learning increased after conducting the supervision technique of classroom observation, among others (a) the ability of teachers in planning the learning is good, (b) the ability of teachers in implementing the learning is already very good so, the situation of class becomes conducive and enjoyable, and (c) the ability of teachers in evaluating the learning also increased to be better.